Introducing New Exponential Zagreb Indices for Graphs - Nihat Akgunes; Busra Aydin (Journal of Mathematics)
New graph invariants, named exponential Zagreb indices, are introduced for more than one type of Zagreb index. After that, in terms of exponential Zagreb indices, lists on equality results over special graphs are presented as well as some new bounds on unicyclic, acyclic, and general graphs are obtained. Moreover, these new graph invariants are determined for some graph operations.